Methodology and clinical utility of ultrasound-guided fine-needle aspiration cytology of lymph nodes in melanoma patients. (April 2013) - Schäfer, Gregor; Eggermont, Alexander MM; Voit, Christiane A
Ultrasound-guided fine-needle aspiration cytology is an evolving method for quick diagnosis of the presence or absence of tumor in lymph nodes in malignant melanoma patients. New criteria for suspicion have greatly improved sensitivity and thus the clinical utility of ultrasound-guided fine-needle aspiration cytology. An earlier diagnosis of the presence of metastasis may lead to earlier surgical and systemic treatments and therefore an improvement of outcome in terms of relapse-free and even overall survival.